2019
DOI: 10.4253/wjge.v11.i2.84
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoscopy in the management of primary sclerosing cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is a rare but prominent fibroinflammatory cholangiopathy which can affect individuals of essentially any age. It carries a median survival of 15-20 years, regardless of age at diagnosis, and is a foremost risk factor for cholangiocarcinoma. Given the chronic and progressive nature of PSC, its inherent risk for biliary tract and other complications, and the paucity of effective pharmacotherapies, endoscopy plays a major role in the care of many patients with this disorder. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Diagnostic and surveillance challenges posed by indeterminate biliary strictures, especially in PSC patients, are well known [18,19]. In the current study, bimodal ERCP unveiled a dominant segmental stricture in a patient with PSC, not otherwise seen on conventional fluoroscopy.…”
Section: Discussionsupporting
confidence: 48%
“…Diagnostic and surveillance challenges posed by indeterminate biliary strictures, especially in PSC patients, are well known [18,19]. In the current study, bimodal ERCP unveiled a dominant segmental stricture in a patient with PSC, not otherwise seen on conventional fluoroscopy.…”
Section: Discussionsupporting
confidence: 48%
“…An earlier study performed by Savader, Prescott, Lund and Osterman on intraductal biliary biopsy concluded that brush cytology and fluoroscopy guided forceps had zero sensitivity for diagnosing bile duct cancer (cholangiocarcinoma), while sensitivity increased to 27% when using direct optical imaging of forceps within the bile duct [8] . More recently a custom single-operator cholangioscope that provides this direct optical imaging and a smaller-sized forceps system were developed, and sensitivity has been improved to be greater than brush biopsy [2] , [9] , [10] . The advent of second generation cholangioscopes and laser-based imaging catheters may provide greater improvements in sensitivity and specificity but have not provided satisfactory diagnostic yield of tissue during cholangiopancretoscopy, which may be addressed with new innovative biopsy tools [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Till now, cytotoxic chemotherapy remains the only therapeutic method for unresectable cholangiocarcinoma (CCA). Unfortunately, CCA resists most chemotherapy, and 5-year overall survival status is extremely poor, remaining at 10% 3,4 . To improve the diagnosis and prognosis of CCA patients, it is crucial to investigate molecular mechanisms to develop biological treatment.…”
Section: Introductionmentioning
confidence: 99%